2010
DOI: 10.1099/vir.0.026351-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-genotype white spot syndrome virus infections of shrimp are inversely correlated with disease outbreaks in ponds

Abstract: Outbreaks of white spot syndrome virus (WSSV) in shrimp culture and the relationship between the virus and virulence are not well understood. Here, we provide evidence showing that WSSV mixed-genotype infections correlate with lower outbreak incidence and that disease outbreaks correlate with single-genotype infections. We tested 573 shrimp samples from 81 shrimp ponds in the Mekong delta with outbreak or non-outbreak status. The variable number tandem repeat (VNTR) loci of WSSV were used as molecular markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
5
36
0
Order By: Relevance
“…Similar to previous observations, mixed infection with two RU types, 4 and 11 was noticed in the present study (Hoa et al, 2005(Hoa et al, , 2011(Hoa et al, , 2012Musthaq et al, 2006;Pradeep et al, 2008). In contrast to the earlier observation which correlated mixed infection with lower virulence (Hoa et al, 2012), in this case the farm with mixed WSSV infection had suffered the similar severity as that of single genotype infection.…”
Section: Snp At 48supporting
confidence: 90%
“…Similar to previous observations, mixed infection with two RU types, 4 and 11 was noticed in the present study (Hoa et al, 2005(Hoa et al, , 2011(Hoa et al, , 2012Musthaq et al, 2006;Pradeep et al, 2008). In contrast to the earlier observation which correlated mixed infection with lower virulence (Hoa et al, 2012), in this case the farm with mixed WSSV infection had suffered the similar severity as that of single genotype infection.…”
Section: Snp At 48supporting
confidence: 90%
“…Factors responsible for virulence are difficult to conclude from confounding reports of difficulties in correlating specific genotypes to shrimp mortality (John et al (Walker et al 2011a,b) or the presence of mixed WSSV genotypes being related inversely to shrimp mortality at farms (Hoa et al 2011). In another study examining WSSV strains from the same geographic region, a WSSV strain containing a 19 kb genome deletion was found to be more virulent, possibly as a result of the smaller genome providing the strain with some advantage in replication (Marks et al 2005).…”
Section: Genotype Stability Following Repeated Passagementioning
confidence: 99%
“…1B−E, Table 1). ORF94 and ORF125 VNTR types have been used widely to distinguish WSSV strains (Wongteerasupaya et al 2003, Hoa et al 2005, 2011, and many WSSV strains have been associated with disease at shrimp farms in India (Syed Musthaq et al 2006, Pradeep et al 2008, John et al 2010, Walker et al 2011a. The VNTR variations detected were thus not unexpected considering the different species examined and the fact that the diseased shrimp had been sourced from different farms in different regions of South India.…”
Section: Genotyping Of Wssv Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, if we consider the diversity for the entire study area and over the 3 years analyzed, the conclusion is that this molecular marker has high variability (0.902), which again means either a high rate of mutation of the viral genome in this region, or the constant introduction or mobility of new WSSV varieties ( Guasave Sur 7-2 and 10-10 Angostura 11-9 and 13-3 Elota 7-7 and 9-10 Elota 7-7 and 10-5 As in other works that have reported double infections with isolates of WSSV and different sizes of the ORF 94 region (Wongteerasupaya et al 2003, Pradeep et al 2008, we found 2 cases, indicating a frequency of only 1.9% during the study period (Table 8). Some research groups have sought to associate this finding with virulence, but results are contradictory (Hoa et al 2011, Walker et al 2011, so its biological role is still unknown. A haplotype lacking the ORF 94 region has been described for Saudi Arabia (Tang et al 2012).…”
Section: Orf 94mentioning
confidence: 99%